Modified polycaprolactone composite scaffold as well as preparation method and application thereof
By loading metal organic frame materials and mesoporous ceramics on the polycaprolactone scaffold, a gradient pore structure is formed, and combined with polydopamine coating, the problems of low degradation efficiency, insufficient drug release and poor cell adhesion in the prior art are solved, and the good biocompatibility and antibacterial properties of the scaffold are achieved, which is suitable for the repair and regeneration of bone tissue defects under infection.
Patent Information
- Application Number
- CN202411952694.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing polycaprolactone-based stents and polydopamine-loaded granules have problems such as low efficiency, poor cell adhesion, single function and complex preparation process in terms of degradation and drug release.
Using a modified polycaprolactone composite scaffold, a gradient pore structure and a multi-layer pore structure are formed by loading metal organic frame materials and mesoporous ceramics on the surface of the polycaprolactone scaffold matrix, and a gradient pore structure is formed, combined with polydopamine coating to improve drug release efficiency.
The good biocompatibility, antibacterial performance and induce osteogenesis and differentiation of stem cells are achieved, especially in the case of infection, and the slow release of drugs that promote tissue regeneration and repair are initiated. It is suitable for the repair and regeneration of bone tissue defects under infection.
Smart Images

Figure CN119770729A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical materials, and specifically relates to a modified polycaprolactone composite material stent and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of bone tissue engineering technology, prostheses prepared by tissue engineering have shown good cartilage repair effects, and there is hope that tissue engineering technology can be used to treat growth plate injuries. Cartilage tissue engineering generally includes scaffolds and active substances. The ideal bone tissue engineering scaffold should have an interconnected porous network structure to provide interconnected channels for cell migration, ion transport, and cell-to-cell interaction. Conventional technologies include foaming, sacrificial template method, freeze-drying method and casting method, etc. 3D printing is also called additive manufacturing technology. Due to its unique and significant advantages in high precision, personalized manufacturing and complex shape construction, 3D printing has penetrated into all walks of life, led innovation, and triggered changes in the global manufacturing industry. 3D printing obtains a three-dimensional entity by stacking raw materials layer by layer on a plane. The porosity and shape of the scaffold can be freely designed, which can well meet the needs of bone tissue engineering.
[0003] Polycaprolactone (PCL) is a commonly used material for 3D printing. It has good biocompatibility, is non-toxic, and is degradable. It also has the function of inducing tissue regeneration and providing a place for cell adhesion, proliferation, and differentiation. It is widely used in the field of medical science. However, due to the hydrophobicity of PCL, the adhesion of the formed scaffold will be affected, and its mechanical structure will be significantly damaged after degradation. The introduction of artificial materials through surface modification, physical doping, chemical grafting, etc. can supplement the characteristics that polycaprolactone does not have. By adjusting its mixed components, the advantages of each component can be maximized, thereby meeting the ideal parameter requirements of bone repair materials. In addition, polydopamine microspheres have a certain drug loading capacity and can be used as a drug carrier for bone tissue engineering technology.
[0004] The existing technologies of bone tissue engineering scaffolds include: Literature [Xu Yingke. Characterization and biocompatibility study of 3D printed polycaprolactone / β-tricalcium phosphate scaffolds loaded with polydopamine microspheres [D]. Hainan Medical College, 2023. DOI: 10.27952 / d.cnki.ghnyx.2023.000017.] reported the preparation of polycaprolactone / β-TCP composite scaffolds loaded with polydopamine microspheres, which can be used as bone repair materials to promote bone repair; Literature [Dong Bo. Research on the repair effect of 3D printed composite scaffolds loaded with FK-16 on infected bone defects [D]. Jilin University, 2024. DOI: 10.27162 / d.cnki.gjlin.2024.005386.] reported that by synthesizing 3D printed hydroxyapatite / polycaprolactone scaffolds with sustainable release of FK-16, bone transplant materials that can be used to effectively repair infected bone defects were obtained. However, the polycaprolactone-based scaffolds and polydopamine drug-loaded particles produced by the above-mentioned prior art generally have the following problems: 1) Polydopamine degrades slowly, making it difficult to effectively release enough drugs to achieve antibacterial and bone-promoting effects; 2) The surface of the polycaprolactone scaffold is too hydrophobic, which is not conducive to cell adhesion and proliferation; 3) The components and functions of the material are relatively simple, making it difficult to achieve good antibacterial and bone regeneration effects; 4) The preparation process is complicated and difficult to industrialize. Summary of the invention
[0005] In order to overcome the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a modified polycaprolactone composite material scaffold. The second purpose of the present invention is to provide a method for preparing the above-mentioned modified polycaprolactone composite material scaffold. The third purpose of the present invention is to provide the application of the above-mentioned modified polycaprolactone composite material scaffold. The gradient pore structure scaffold of the present invention not only has good porosity and biocompatibility, antibacterial properties, and induces osteogenic differentiation of stem cells, but also can accelerate the release of antibacterial drugs, especially in the case of infection, and initiate the slow release of internally encapsulated drugs that promote tissue regeneration and repair, and is suitable for the repair and regeneration of bone tissue defects under infection.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a modified polycaprolactone composite material stent, comprising a polycaprolactone stent matrix, the surface of the polycaprolactone stent matrix is loaded with a metal organic framework material, and the metal organic framework material is loaded with antibacterial drugs; the surface and interior of the polycaprolactone stent matrix are distributed with interconnected pores, and the pores gradually increase from the surface of the polycaprolactone stent matrix to the inside; the polycaprolactone stent matrix is distributed with drug-loaded materials, and the drug-loaded materials include mesoporous ceramics, the interior of the mesoporous ceramics is filled with tissue regeneration and repair drugs, and the surface of the mesoporous ceramics is coated with polydopamine.
[0008] The pores of the stent in the present invention gradually increase from the surface to the inside of the polycaprolactone stent matrix, forming gradient pores and a multi-level pore structure, wherein the internal pores of the polycaprolactone stent matrix refer to the pores formed by stacking between fibers (macroscopic pores, hundreds of microns), and the external pores of the polycaprolactone stent matrix are the pores formed on the fibers due to pore-forming technology (microscopic pores, several to tens of microns).
[0009] Preferably, the surface of the polycaprolactone composite material has pores with a size of 1-100 μm.
[0010] Preferably, the mesoporous ceramic is selected from at least one of mesoporous silicon, mesoporous calcium silicate, mesoporous magnesium silicate, mesoporous zinc silicate, mesoporous strontium silicate, mesoporous bioglass, and mesoporous hydroxyapatite.
[0011] Preferably, the mesoporous ceramics are particles with a particle size of 30 to 1500 nm.
[0012] More preferably, the specific surface area of the mesoporous ceramic is 100 to 2000 m 2 / g, and the average pore size is 2 to 50 nm.
[0013] Preferably, the metal organic framework material is a zeolite imidazolate framework material self-assembled by coordination of zinc ions and 2-methylimidazole.
[0014] Preferably, the drug promoting tissue regeneration and repair is selected from at least one of bone morphogenetic protein-2, bone morphogenetic protein-7, vascular endothelial cell factor, platelet-derived factor, curcumin, melatonin, alendronate sodium, naringin, resveratrol, dexamethasone, gentamicin sulfate, epidermal growth factor, fibroblast growth factor, keratinocyte growth factor, nerve growth factor, berberine hydrochloride, gentamicin, transforming growth factor, insulin-like growth factor, parathyroid hormone, growth hormone, interleukin, alendronate sodium, salmon calcitonin, zoledronic acid sodium, ibandronate sodium, strontium ranelate, and vitamin D.
[0015] Preferably, the antibacterial drug is at least one of ertapenem, imipenem, meropenem, piperacillin / tazobactam, amikacin, colistin, polymyxin B, amikacin, linezolid, vancomycin, tetracycline, tigecycline, fluorouracil, amphotericin B, caspofungin, voriconazole, triclosan, chlorhexidine, penicillin, roxithromycin, clarithromycin, azithromycin, tobramycin, etimicin, netilmicin, tetracycline, chloramphenicol, ciprofloxacin, levofloxacin, moxifloxacin, metronidazole, ornidazole, tinidazole, itraconazole, mycobacterium, and griseofulvin.
[0016] Preferably, the molecular weight of the polycaprolactone is 30,000 to 100,000 Daltons.
[0017] The second aspect of the present invention provides a method for preparing the modified polycaprolactone composite material bracket of the first aspect, comprising the following steps:
[0018] S1. Mixing the drug-carrying material, gluconolactone and polycaprolactone in a solvent to obtain a mixed solution, transferring the solution to a mold and placing the solution for a period of time to obtain a mixed material film; using the mixed material film as a printing material, 3D printing to obtain a scaffold with a gradient pore structure; after printing, immersing the scaffold with a gradient pore structure in water to remove gluconolactone and residual solvent;
[0019] S2. Reacting the scaffold with a gradient pore structure, an antibacterial drug, 2-methylimidazole and a zinc source in water to obtain the modified polycaprolactone composite material scaffold.
[0020] Preferably, the method for preparing the drug-loaded material comprises the following steps: immersing the mesoporous ceramic in a solution containing a drug for promoting tissue regeneration and repair to obtain a mesoporous ceramic encapsulating the drug for promoting tissue regeneration and repair; immersing the mesoporous bioceramic encapsulating the drug for promoting tissue regeneration and repair in a solution containing dopamine to obtain a drug-loaded material.
[0021] More preferably, the solvent of the solution containing the drug for promoting tissue regeneration and repair is water.
[0022] More preferably, the mass ratio of the mesoporous ceramic, the regeneration and repair promoting drug and dopamine is (50-1000):(0.005-10):100.
[0023] Preferably, the mass ratio of the drug-carrying material to polycaprolactone is (0.005-0.05):1.
[0024] Preferably, the mass ratio of gluconolactone to polycaprolactone is (0.5-3):1.
[0025] Preferably, the solvent is dichloromethane.
[0026] Preferably, the process conditions for 3D printing satisfy at least one of the following:
[0027] a) 3D printing uses a printing needle with a diameter of 0.15-0.4mm;
[0028] b) Printing and heating temperature: barrel 60~80℃, needle 60~90℃;
[0029] c) Fiber spacing 0.8mm×0.8mm; printing speed 8~17mm / s;
[0030] d) Air pressure is 320-400Kpa;
[0031] e) The height of the stent layer is 75-95% of the needle diameter;
[0032] f) The fiber orientation is "0-90°".
[0033] The fiber spacing refers to the distance between the mid-axes of adjacent fibers in the horizontal and vertical directions. The fiber orientation refers to the angle between the upper and lower layers of fibers. The support layer height refers to the layer thickness of the printed layers.
[0034] Preferably, in step S1, the mixing time is 30-100 hours.
[0035] More preferably, the mixing is performed under stirring conditions, wherein the stirring rate is 100 to 1000 rpm.
[0036] Preferably, the placement time is 50-100 hours.
[0037] Preferably, the film-forming condition of the mixed material film is volatilization film-forming.
[0038] Preferably, the mass ratio of the 2-methylimidazole, the antibacterial drug and the zinc source is (18-23):(4-10):1.
[0039] Preferably, the zinc source is zinc nitrate.
[0040] Preferably, step S2 specifically comprises the following steps: adding the scaffold with a gradient pore structure into an aqueous solution containing an antibacterial drug and 2-methylimidazole for dispersion, slowly adding a zinc source for reaction, and washing and freeze-drying after the reaction to obtain a modified polycaprolactone composite material scaffold.
[0041] The third aspect of the present invention provides the use of the modified polycaprolactone composite material scaffold of the first aspect in the preparation of a product for promoting bone tissue repair and regeneration.
[0042] The beneficial effects of the present invention are:
[0043] The invention provides a modified polycaprolactone composite material stent, comprising a polycaprolactone composite material stent; the polycaprolactone composite material stent has a porous structure, wherein the pores on the surface and inside are interconnected, and the pore size increases gradually from the surface to the inside, so that the printed stent simultaneously obtains macroscopic large pores (fiber gaps) and microscopic small pores (fiber surface holes), which can not only improve the surface roughness of the stent, achieve the purpose of significantly promoting the adhesion of stent cells, but also significantly increase the specific surface area of the stent, accelerate the degradation of polycaprolactone and release more acidic degradation products, thereby accelerating the degradation of polydopamine and accelerating the release of drugs embedded therein, solving the problem of slow degradation of polydopamine in vivo and in vitro.
[0044] The specific beneficial effects are as follows:
[0045] (1) The surface of the modified polycaprolactone composite material scaffold of the present invention is also loaded with a metal organic framework material loaded with antibacterial drugs. The drug-loaded metal organic framework material can not only enhance the antibacterial properties of the gradient pore structure polycaprolactone scaffold, but also enable the internal tissue regeneration and repair drugs to be slowly released. In the case of bone infection, the pH in the local microenvironment is low, which will significantly accelerate the degradation of the metal organic framework material and accelerate the release of the antibacterial drugs loaded therein, synergistically achieving better antibacterial and bone regeneration effects. In addition, the polycaprolactone composite material scaffold of the present invention has microscopic pores, which provide more sites for the deposition of the drug-loaded metal organic framework material, which is conducive to further enhancing the biological activity of the scaffold.
[0046] (2) The modified polycaprolactone composite material scaffold of the present invention uses drug-loaded mesoporous ceramics as the scaffold forming material, which can enhance the mechanical strength of the scaffold and the drug-loaded material, making it suitable for bone repair. The modified polycaprolactone composite material scaffold of the present invention further disperses the drug that promotes tissue regeneration and repair inside the polycaprolactone, and compared with the conventional use of the adhesive effect of the polydopamine coating to adsorb and load the drug, the drug can be sustained and controlled to achieve a better therapeutic effect.
[0047] (3) The present invention provides a method for preparing the modified polycaprolactone composite material scaffold. The preparation method is simple and feasible. The use of gluconolactone as a pore-forming agent can make the scaffold have a gradient pore structure, so that the printed scaffold can simultaneously obtain macroscopic large pores (fiber gaps) and microscopic small pores (holes on the fiber surface). Gluconolactone is easily soluble in water and can be easily eliminated after the reaction.
[0048] (4) The modified polycaprolactone composite material scaffold of the present invention has great application potential in the preparation of products that promote bone tissue repair and regeneration. The surface-modified gradient pore structure scaffold has good porosity and biocompatibility, antibacterial properties, and the characteristics of inducing stem cell osteogenic differentiation. Under infection conditions, the metal organic framework material can accelerate the release of antibacterial drugs, and then initiate the slow release of the internally encapsulated drugs that promote tissue regeneration and repair. Therefore, it is suitable for the repair and regeneration of bone tissue defects under infection. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 The release performance of the drug for promoting tissue regeneration and repair in vitro of the materials prepared in the examples and comparative examples;
[0050] Figure 2 The release performance of the drug for promoting tissue regeneration and repair in vitro of the materials prepared in Example 1 and the comparative example;
[0051] Figure 3 The in vitro antimicrobial drug release performance of the materials prepared in the examples and comparative examples;
[0052] Figure 4The in vitro antimicrobial drug release performance of the materials prepared in Example 1 and the comparative example;
[0053] Figure 5 The alkaline phosphatase activity of the scaffolds prepared in the examples and comparative examples. DETAILED DESCRIPTION
[0054] The present invention is further described in detail below through specific examples. The raw materials used in the following examples, unless otherwise specified, can be obtained from conventional commercial sources or prepared and separated by simple synthesis; the processes used, unless otherwise specified, are conventional processes in the art.
[0055] Example 1
[0056] This embodiment provides a modified polycaprolactone composite material bracket, and the preparation method thereof is as follows:
[0057] S1. At 0°C, 1000 mg of mesoporous zinc silicate (average particle size between 300 nm and 800 nm, specific surface area between 400 m 2 / g~900m 2 / g, with an average pore size between 30nm and 50nm) was dispersed in 100mL of an aqueous solution containing 0.2mg of bone morphogenetic protein-2, stirred at 200rpm for 18h, and freeze-dried to obtain a mesoporous material loaded with a therapeutic agent; at 0°C, 300mg of the mesoporous material loaded with a therapeutic agent was dispersed in 100mL of an aqueous solution of 2mg / mL dopamine (pH=8.5), stirred at 200rpm for 10min, and freeze-dried to obtain a polydopamine-encapsulated drug-loaded mesoporous material.
[0058] S2. Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 100mL of dichloromethane, add 10g of gluconolactone and 150mg of drug-loaded mesoporous ceramics@polydopamine particles, and stir magnetically at 300rpm for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone film.
[0059] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 60℃, the needle temperature is 65℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 380Kpa, and the scaffold layer height is 80% of the needle diameter, and the gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold is printed layer by layer. 20mg of gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold was soaked in 10mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold.
[0060] S4. The gradient pore structure scaffold was added into 12 mL of 41 mg / mL 2-methylimidazole aqueous solution (containing 15 mg / mL vancomycin), and 2 mL of 12 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the scaffold was washed and freeze-dried to obtain a drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold with a gradient pore structure and a drug-loaded ZIF8 surface modified thereon.
[0061] The modified polycaprolactone composite material scaffold prepared in Example 1 has a porous structure, and the pores of the scaffold gradually increase from the surface to the inside of the polycaprolactone scaffold matrix, wherein the internal pores of the polycaprolactone scaffold matrix refer to the pores formed by the stacking of fibers (macro pores, hundreds of microns), and the external pores of the polycaprolactone scaffold matrix are the pores formed on the fibers due to the pore-forming technology (micro pores, several to tens of microns).
[0062] Example 2
[0063] This embodiment provides a modified polycaprolactone composite material bracket, and the preparation method thereof is as follows:
[0064] S1. At 37°C, 1000 mg of mesoporous bioglass (average particle size between 400 nm and 600 nm, specific surface area between 100 m 2 / g~700m 2 / g, with an average pore size between 10nm and 30nm) was dispersed in 100mL of an aqueous solution containing 100mg of dexamethasone, stirred at 500rpm for 4h, and freeze-dried to obtain a mesoporous material loaded with a therapeutic agent; at 37°C, 900mg of the mesoporous material loaded with a therapeutic agent was dispersed in 100mL of an aqueous solution of 3mg / mL dopamine (pH=8.4), stirred at 100rpm for 20min, and freeze-dried to obtain a drug-loaded mesoporous material wrapped with polydopamine.
[0065] S2. Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 20mL of dichloromethane, add 20g of gluconolactone and 50mg of drug-loaded mesoporous ceramics@polydopamine particles, and stir magnetically at 600pm for 60h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 48h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone film.
[0066] S3. Put the film into the printing barrel, with a needle diameter of 0.3 mm, a barrel temperature of 70°C, a needle temperature of 75°C, a fiber spacing of 0.8 mm×0.8 mm, a printing rate of 8 mm / s, a fiber orientation of "0-90°", an air pressure of 320 Kpa, and a scaffold layer height of 85% of the needle diameter, and print gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone scaffolds layer by layer.
[0067] S4, soak 20mg of gluconolactone / drug-loaded mesoporous ceramic @ polydopamine particles / polycaprolactone scaffold in 25mL aqueous solution, ultrasonicate at room temperature for 0.4 hours to obtain gradient pore structure drug-loaded mesoporous ceramic @ polydopamine particles / polycaprolactone scaffold. Add the gradient pore structure scaffold to 13mL 38mg / mL 2-methylimidazole aqueous solution (containing 18mg / mL chloramphenicol), add 1mL 24mg / mL zinc nitrate aqueous solution dropwise while stirring, wash and freeze-dry after reaction, and obtain gradient pore structure, drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold with drug-loaded ZIF8 surface modification.
[0068] Example 3
[0069] This embodiment provides a modified polycaprolactone composite material bracket, and the preparation method thereof is as follows:
[0070] S1. At 20°C, 500 mg of mesoporous silica (average particle size between 30 nm and 600 nm, specific surface area between 500 m 2 / g~2000m 2 / g, with an average pore size between 2nm and 6nm) was dispersed in 50mL of an aqueous solution containing 30mg of curcumin, stirred at 100rpm for 24h, and freeze-dried to obtain a mesoporous material loaded with a therapeutic agent; at 30°C, 150mg of the mesoporous material loaded with a therapeutic agent was dispersed in 100mL of an aqueous solution of 1mg / mL dopamine (pH=8), stirred at 400rpm for 15h, and freeze-dried to obtain a polydopamine-encapsulated drug-loaded mesoporous material.
[0071] S2. Dissolve 10g of polycaprolactone (molecular weight: 100,000 Daltons) in 125mL of dichloromethane, add 30g of gluconolactone and 110mg of drug-loaded mesoporous ceramics @ polydopamine particles, and mechanically stir at 800rpm for 36h to obtain a gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 48h to obtain a gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone film.
[0072] S3, put the film into the printing barrel, the needle diameter is 0.15mm, the barrel temperature is 80℃, the needle temperature is 60℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 12mm / s, the fiber orientation is "0-90°", the air pressure is 400Kpa, and the scaffold layer height is 95% of the needle diameter, and the gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold is printed layer by layer. 20mg of gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold was soaked in 50mL of aqueous solution, and ultrasonicated at room temperature for 1 hour to obtain a gradient pore structure drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold.
[0073] S4. The gradient pore structure scaffold is added to 12 mL of a 34 mg / mL 2-methylimidazole aqueous solution (containing 25 mg / mL chlorhexidine), and 3 mL of a 7 mg / mL zinc nitrate aqueous solution is added dropwise during stirring. After the reaction, the scaffold is washed and freeze-dried to obtain a drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold with a gradient pore structure and a drug-loaded ZIF8 surface modified thereon.
[0074] Example 4
[0075] This embodiment provides a modified polycaprolactone composite material bracket, and the preparation method thereof is as follows:
[0076] S1. At 30°C, 1000 mg of mesoporous hydroxyapatite (average particle size between 1000 nm and 1500 nm, specific surface area between 100 m 2 / g~500m 2 / g, with an average pore size between 2nm and 10nm) was dispersed in 100mL of an aqueous solution containing 80mg of resveratrol, stirred at 400rpm for 8h, and freeze-dried to obtain a mesoporous material loaded with a therapeutic agent; at 20°C, 600mg of the mesoporous material loaded with a therapeutic agent was dispersed in 100mL of an aqueous solution of 1.5mg / mL dopamine (pH=9), stirred at 600rpm for 2h, and freeze-dried to obtain a drug-loaded mesoporous material wrapped with polydopamine.
[0077] S2. Dissolve 10g polycaprolactone (molecular weight: 60,000 Daltons) in 50mL dichloromethane, add 5g gluconolactone and 80mg drug-loaded mesoporous ceramics @ polydopamine particles, and mechanically stir at 400rpm for 54h to obtain a gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 60h to obtain a gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone film.
[0078] S3, put the film into the printing barrel, with a needle diameter of 0.4mm, a barrel temperature of 75℃, a needle temperature of 90℃, a fiber spacing of 0.8mm×0.8mm, a printing rate of 17mm / s, a fiber orientation of "0-90°", an air pressure of 360Kpa, and a scaffold layer height of 75% of the needle diameter, and print gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds layer by layer. Soak 20mg of gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds in 4mL of aqueous solution, and ultrasonicate at room temperature for 0.5 hours to obtain gradient pore structure drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffolds.
[0079] S4. The gradient pore structure scaffold was added into 16 mL of 53 mg / mL 2-methylimidazole aqueous solution (containing 10 mg / mL penicillin), and 4 mL of 10 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the scaffold was washed and freeze-dried to obtain a drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold with a gradient pore structure and a drug-loaded ZIF8 surface modified thereon.
[0080] Comparative Example 1
[0081] This comparative example provides a method for preparing a ZIF8 surface-modified polycaprolactone scaffold, which is substantially the same as Example 1, except that gluconolactone is not used. The specific preparation method is as follows:
[0082] S1. At 0°C, 1000 mg of mesoporous zinc silicate (average particle size between 300 nm and 800 nm, specific surface area between 400 m 2 / g~900m 2 / g, with an average pore size between 30nm and 50nm) was dispersed in 100mL of an aqueous solution containing 0.2mg of bone morphogenetic protein-2, stirred at 200rpm for 18h, and freeze-dried to obtain a mesoporous material loaded with a therapeutic agent; at 0°C, 300mg of the mesoporous material loaded with a therapeutic agent was dispersed in 100mL of an aqueous solution of 2mg / mL dopamine (pH=8.5), stirred at 200rpm for 10min, and freeze-dried to obtain a polydopamine-encapsulated drug-loaded mesoporous material.
[0083] S2. Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 100mL of dichloromethane, add 150mg of drug-loaded mesoporous ceramics @ polydopamine particles, and stir magnetically at 300rpm for 72h to obtain a drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72h to obtain a drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone film.
[0084] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 60℃, the needle temperature is 65℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 380Kpa, and the scaffold layer height is 80% of the needle diameter, and the drug-loaded mesoporous ceramic @ polydopamine particles / polycaprolactone scaffold is printed layer by layer. 20mg of drug-loaded mesoporous ceramic @ polydopamine particles / polycaprolactone scaffold was soaked in 10mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain the drug-loaded mesoporous ceramic @ polydopamine particles / polycaprolactone scaffold.
[0085] S4. The scaffold was added into 12 mL of 41 mg / mL 2-methylimidazole aqueous solution (containing 15 mg / mL vancomycin), and 2 mL of 12 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the scaffold was washed and freeze-dried to obtain a drug-loaded ZIF8 surface-modified drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold.
[0086] The modified polycaprolactone composite material stent prepared in Comparative Example 1 has a relatively smooth surface, with occasional holes ranging from a few microns to tens of microns.
[0087] Comparative Example 2
[0088] This comparative example provides a preparation method of a polycaprolactone scaffold with a gradient pore structure, which is substantially the same as Example 1, except that: no surface modification of ZIF8 is performed. The preparation method is specifically as follows:
[0089] S1. At 0°C, 1000 mg of mesoporous zinc silicate (average particle size between 300 nm and 800 nm, specific surface area between 400 m 2 / g~900m 2 / g, with an average pore size between 30nm and 50nm) was dispersed in 100mL of an aqueous solution containing 0.2mg of bone morphogenetic protein-2, stirred at 200rpm for 18h, and freeze-dried to obtain a mesoporous material loaded with a therapeutic agent; at 0°C, 300mg of the mesoporous material loaded with a therapeutic agent was dispersed in 100mL of an aqueous solution of 2mg / mL dopamine (pH=8.5), stirred at 200rpm for 10min, and freeze-dried to obtain a polydopamine-encapsulated drug-loaded mesoporous material.
[0090] S2. Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 100mL of dichloromethane, add 10g of gluconolactone and 150mg of drug-loaded mesoporous ceramics@polydopamine particles, and stir magnetically at 300rpm for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone film.
[0091] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 60℃, the needle temperature is 65℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 380Kpa, and the scaffold layer height is 80% of the needle diameter, and the gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold is printed layer by layer. 20mg of gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold was soaked in 10mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold.
[0092] S4. Add the gradient pore structure scaffold into 12 mL of an aqueous solution containing 15 mg / mL vancomycin, etc., wash, and freeze-dry to obtain a drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold with a gradient pore structure and surface drug loading.
[0093] Comparative Example 3
[0094] This comparative example provides a method for preparing a polycaprolactone stent, which is substantially the same as Example 1, except that: ZIF8 is not loaded with drugs. The specific preparation method is as follows:
[0095] S1. At 0°C, 1000 mg of mesoporous zinc silicate (average particle size between 300 nm and 800 nm, specific surface area between 400 m 2 / g~900m 2 / g, with an average pore size between 30nm and 50nm) was dispersed in 100mL of an aqueous solution containing 0.2mg of bone morphogenetic protein-2, stirred at 200rpm for 18h, and freeze-dried to obtain a mesoporous material loaded with a therapeutic agent; at 0°C, 300mg of the mesoporous material loaded with a therapeutic agent was dispersed in 100mL of an aqueous solution of 2mg / mL dopamine (pH=8.5), stirred at 200rpm for 10min, and freeze-dried to obtain a polydopamine-encapsulated drug-loaded mesoporous material.
[0096] S2. Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 100mL of dichloromethane, add 10g of gluconolactone and 150mg of drug-loaded mesoporous ceramics@polydopamine particles, and stir magnetically at 300rpm for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone film.
[0097] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 60℃, the needle temperature is 65℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 380Kpa, and the scaffold layer height is 80% of the needle diameter, and the gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold is printed layer by layer. 20mg of gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold was soaked in 10mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold.
[0098] S4. The gradient pore structure scaffold was added into 12 mL of 41 mg / mL 2-methylimidazole aqueous solution, and 2 mL of 12 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the scaffold was washed and freeze-dried to obtain a drug-loaded mesoporous ceramic @ polydopamine / polycaprolactone scaffold with a gradient pore structure and a ZIF8 surface modification.
[0099] Comparative Example 4
[0100] This comparative example provides a preparation method of a polycaprolactone stent, which is substantially the same as Example 1, except that it does not contain drug-loaded ZIF8. The specific preparation method is as follows:
[0101] S1. At 0°C, 1000 mg of mesoporous zinc silicate (average particle size between 300 nm and 800 nm, specific surface area between 400 m 2 / g~900m 2 / g, with an average pore size between 30nm and 50nm) was dispersed in 100mL of an aqueous solution containing 0.2mg of bone morphogenetic protein-2, stirred at 200rpm for 18h, and freeze-dried to obtain a mesoporous material loaded with a therapeutic agent; at 0°C, 300mg of the mesoporous material loaded with a therapeutic agent was dispersed in 100mL of an aqueous solution of 2mg / mL dopamine (pH=8.5), stirred at 200rpm for 10min, and freeze-dried to obtain a polydopamine-encapsulated drug-loaded mesoporous material.
[0102] S2. Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 100mL of dichloromethane, add 10g of gluconolactone and 150mg of drug-loaded mesoporous ceramics@polydopamine particles, and stir magnetically at 300rpm for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72h to obtain a gluconolactone / drug-loaded mesoporous ceramics@polydopamine particles / polycaprolactone film.
[0103] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 60℃, the needle temperature is 65℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 380Kpa, and the scaffold layer height is 80% of the needle diameter, and the gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold is printed layer by layer. 20mg of gluconolactone / drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold was soaked in 10mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure drug-loaded mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold.
[0104] Comparative Example 5
[0105] This comparative example provides a method for preparing a polycaprolactone stent, which is substantially the same as Example 1, except that: the bioactive ceramic@polydopamine particles are not loaded with drugs. The specific preparation method is as follows:
[0106] S1. At 0°C, 1000 mg of mesoporous zinc silicate (average particle size between 300 nm and 800 nm, specific surface area between 400 m 2 / g~900m 2 / g, average pore size between 30nm and 50nm) was dispersed in 100mL of aqueous solution, stirred at 200rpm for 18h, and freeze-dried; at 0°C, 300mg of loaded mesoporous material was dispersed in 100mL of 2mg / mL dopamine aqueous solution (pH=8.5), stirred at 200rpm for 10min, and freeze-dried to obtain polydopamine-coated mesoporous material.
[0107] S2. Dissolve 10g of polycaprolactone (molecular weight: 40,000 Daltons) in 100mL of dichloromethane, add 10g of gluconolactone and 150mg of mesoporous ceramics@polydopamine particles, and stir magnetically at 300rpm for 72h to obtain a gluconolactone / mesoporous ceramics@polydopamine particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72h to obtain a gluconolactone / mesoporous ceramics@polydopamine particles / polycaprolactone film.
[0108] S3, put the film into the printing barrel, with a needle diameter of 0.25mm, a barrel temperature of 60℃, a needle temperature of 65℃, a fiber spacing of 0.8mm×0.8mm, a printing rate of 10mm / s, a fiber orientation of "0-90°", an air pressure of 380Kpa, and a scaffold layer height of 80% of the needle diameter, and print the gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold layer by layer. Soak 20mg of gluconolactone / mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold in 10mL of aqueous solution, and ultrasonicate at room temperature for 0.5 hours to obtain a gradient pore structure mesoporous ceramics @ polydopamine particles / polycaprolactone scaffold.
[0109] S4. The gradient pore structure scaffold was added into 12 mL of 41 mg / mL 2-methylimidazole aqueous solution (containing 15 mg / mL vancomycin), and 2 mL of 12 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the scaffold was washed and freeze-dried to obtain a mesoporous ceramic @ polydopamine / polycaprolactone scaffold with a gradient pore structure and a drug-loaded ZIF8 surface modified thereon.
[0110] Comparative Example 6
[0111] This comparative example provides a method for preparing a polycaprolactone stent, which is substantially the same as Example 1, except that the drug-loaded polydopamine particles do not contain bioactive ceramics. The specific preparation method is as follows:
[0112] S1. At 0°C, 0.2 mg of bone morphogenetic protein-2 was dissolved in 1000 mL of 2 mg / mL dopamine aqueous solution (pH=8.5), stirred at 200 rpm for 10 min, and freeze-dried to obtain drug-loaded polydopamine particles.
[0113] S2. Dissolve 10 g of polycaprolactone (molecular weight: 40,000 Daltons) in 100 mL of dichloromethane, add 10 g of gluconolactone and 150 mg of drug-loaded polydopamine, and stir magnetically at 300 rpm for 72 h to obtain a gluconolactone / drug-loaded polydopamine / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72 h to obtain a gluconolactone / drug-loaded polydopamine / polycaprolactone film.
[0114] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 60℃, the needle temperature is 65℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 380Kpa, and the scaffold layer height is 80% of the needle diameter, and the gluconolactone / drug-loaded polydopamine / polycaprolactone scaffold is printed layer by layer. 20mg of gluconolactone / drug-loaded polydopamine / polycaprolactone scaffold is soaked in 10mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure drug-loaded polydopamine / polycaprolactone scaffold.
[0115] S4. The gradient pore structure scaffold was added to 12 mL of 41 mg / mL 2-methylimidazole aqueous solution (containing 15 mg / mL vancomycin), and 2 mL of 12 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the scaffold was washed and freeze-dried to obtain a drug-loaded polydopamine / polycaprolactone scaffold with a gradient pore structure and a drug-loaded ZIF8 surface modified thereon.
[0116] Comparative Example 7
[0117] This comparative example provides a method for preparing a polycaprolactone scaffold, which is substantially the same as Example 1, except that it does not contain polydopamine. The specific preparation method is as follows:
[0118] S1. At 0°C, 1000 mg of mesoporous zinc silicate (average particle size between 300 nm and 800 nm, specific surface area between 400 m 2 / g~900m 2 / g, with an average pore size between 30nm and 50nm) were dispersed in 100mL of an aqueous solution containing 0.2mg of bone morphogenetic protein-2, stirred at 200rpm for 18h, and freeze-dried to obtain drug-loaded mesoporous ceramics.
[0119] S2. Dissolve 10 g of polycaprolactone (molecular weight: 40,000 Daltons) in 100 mL of dichloromethane, add 10 g of gluconolactone and 150 mg of drug-loaded mesoporous ceramic particles, and stir magnetically at 300 rpm for 72 h to obtain a gluconolactone / drug-loaded mesoporous ceramic particles / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72 h to obtain a gluconolactone / drug-loaded mesoporous ceramic particles / polycaprolactone film.
[0120] S3, put the film into the printing barrel, the needle diameter is 0.25mm, the barrel temperature is 60℃, the needle temperature is 65℃, the fiber spacing is 0.8mm×0.8mm, the printing rate is 10mm / s, the fiber orientation is "0-90°", the air pressure is 380Kpa, and the scaffold layer height is 80% of the needle diameter, and the gluconolactone / drug-loaded mesoporous ceramic particles / polycaprolactone scaffold is printed layer by layer. 20mg of gluconolactone / drug-loaded mesoporous ceramic particles / polycaprolactone scaffold is soaked in 10mL of aqueous solution, and ultrasonicated at room temperature for 0.5 hours to obtain a gradient pore structure drug-loaded mesoporous ceramic particles / polycaprolactone scaffold.
[0121] S4. The gradient pore structure scaffold was added into 12 mL of 41 mg / mL 2-methylimidazole aqueous solution (containing 15 mg / mL vancomycin), and 2 mL of 12 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the scaffold was washed and freeze-dried to obtain a drug-loaded mesoporous ceramic / polycaprolactone scaffold with a gradient pore structure and a drug-loaded ZIF8 surface modified thereon.
[0122] Comparative Example 8
[0123] This comparative example provides a method for preparing a polycaprolactone stent, which is substantially the same as Example 1, except that it does not contain drug-loaded mesoporous ceramic@polydopamine particles. The specific preparation method is as follows:
[0124] S1. Dissolve 10 g of polycaprolactone (molecular weight: 40,000 Daltons) in 100 mL of dichloromethane, add 10 g of gluconolactone, and stir magnetically at 300 rpm for 72 h to obtain a gluconolactone / polycaprolactone solution. Pour the solution onto a glass culture dish and place it in a ventilated state for 72 h to obtain a gluconolactone / polycaprolactone film.
[0125] S2. The film is placed in a printing barrel, with a needle diameter of 0.25 mm, a barrel temperature of 60°C, a needle temperature of 65°C, a fiber spacing of 0.8 mm×0.8 mm, a printing rate of 10 mm / s, a fiber orientation of "0-90°", an air pressure of 380 Kpa, and a scaffold layer height of 80% of the needle diameter, and the gluconolactone / polycaprolactone scaffold is printed layer by layer. 20 mg of the gluconolactone / polycaprolactone scaffold is soaked in 10 mL of aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain a polycaprolactone scaffold with a gradient pore structure.
[0126] S4. The gradient pore structure scaffold was added to 12 mL of 41 mg / mL 2-methylimidazole aqueous solution (containing 15 mg / mL vancomycin), and 2 mL of 12 mg / mL zinc nitrate aqueous solution was added dropwise during stirring. After the reaction, the scaffold was washed and freeze-dried to obtain a polycaprolactone scaffold with a gradient pore structure and a drug-loaded ZIF8 surface modified thereon.
[0127] Comparative Example 9
[0128] This comparative example provides a preparation method of a polycaprolactone stent, which is substantially the same as Example 1, except that it does not contain drug-loaded mesoporous ceramic@polydopamine particles, gluconolactone and drug-loaded ZIF8. The specific preparation method is as follows:
[0129] 10g of polycaprolactone (molecular weight: 40,000 Daltons) was placed in a printing barrel, with a needle diameter of 0.25mm, a barrel temperature of 60°C, a needle temperature of 65°C, a fiber spacing of 0.8mm×0.8mm, a printing rate of 10mm / s, a fiber orientation of "0-90°", an air pressure of 380Kpa, and a scaffold layer height of 80% of the needle diameter, and the gluconolactone / polycaprolactone scaffold was printed layer by layer. 20mg of the gluconolactone / polycaprolactone scaffold was soaked in 10mL of aqueous solution and ultrasonicated at room temperature for 0.5 hours to obtain a polycaprolactone scaffold.
[0130] Experimental analysis
[0131] The scaffold materials prepared in the examples and comparative examples were evaluated for their performance as follows: Figures 1-2 and Tables 1 to 3.
[0132] 1. In vitro cytotoxicity evaluation
[0133] The prepared gel was evaluated and scored according to the requirements of GB / T 16886.5.
[0134] L929 mouse fibroblasts that had been cultured for 24 hours and were growing vigorously were digested and prepared to a density of 1.0×10 5 100 μL / mL was inoculated in a 96-well plate. After the cells grew into a monolayer, the original culture medium was removed and 100 μL of the test sample extract, blank control solution, positive control solution and negative control solution were added respectively, with 6 replicates in each group. After the addition of samples, the 96-well plate was placed in a 37°C, 5% CO2 incubator for 24 hours.
[0135] After 24 hours of culture, the original culture medium was aspirated, and 50 μL of MTT (1 mg / mL) was added to each well. The culture was continued for 2 hours. After the end, the supernatant was aspirated and 100 μL of 99.5% pure isopropanol was added to dissolve the crystals; the absorbance value was measured on an ELISA instrument with 570 nm as the main absorption wavelength and 650 nm as the reference wavelength to calculate the cell survival rate.
[0136] The cell viability was calculated according to the following formula: Cell viability (%) = 100 × OD 570e / OD570 b
[0137] OD 570eIt is the average optical density of the test sample or control sample extract.
[0138] OD 570b is the average optical density of the blank.
[0139] The experimental results are shown in Table 1:
[0140] Table 1 In vitro cell survival rate of the scaffolds prepared in the examples and comparative examples
[0141]
[0142] 2. Hemolytic performance test
[0143] Blood was collected from the heart of healthy rabbits according to the amount of blood used in the experiment. For example, 10 mL of blood was collected, and 0.5 mL of potassium oxalate solution with a mass concentration of 20 g / L was added to prepare fresh anticoagulated rabbit blood. Take 8 mL of fresh anticoagulated rabbit blood and dilute it with 10 mL of sodium chloride injection with a mass concentration of 9 g / L. The test sample group was added with the test sample according to the extraction ratio, and then 10 mL of sodium chloride injection was added; 10 mL of sodium chloride was added to each tube of the negative control group; 10 mL of distilled water was added to each tube of the positive control group. Three tubes were operated in parallel for each group. After all the test tubes were placed in a constant temperature water bath at (37±1)℃ for 30 minutes, 0.2 mL of diluted rabbit blood was added to each test tube, gently mixed, and placed in a (37±1)℃ water bath for another 60 minutes. Pour out the liquid in the tube and centrifuge at 800g for 5 minutes. Aspirate the supernatant and transfer it to a cuvette, and measure the absorbance at a wavelength of 545 nm using a spectrophotometer. The absorbance of the test group and the control group is the average of the three tubes. The absorbance of the negative control tube should not be greater than 0.03; the absorbance of the positive control tube should be 0.8±0.3, otherwise the test should be repeated. Calculate according to the following formula: Hemolysis rate = (absorbance of the test group - absorbance of the negative control group) / (absorbance of the positive control group - absorbance of the negative control group) × 100%, the results are shown in Table 2:
[0144] Table 2 Hemolysis rate of materials obtained in Examples and Comparative Examples
[0145]
[0146] From the hemolysis rate evaluation results of the examples and comparative examples (Table 2), it can be seen that the hemolysis rate of the hydrogel prepared by the method of the present invention is less than 5%, and there is no hemolysis risk.
[0147] 3. In vitro drug release performance test
[0148] The in vitro drug release performance evaluation method is as follows: 500 mg of the product is immersed in 200 mL of PBS (pH = 7.4) in a constant temperature shaker at 37°C and 60 rpm, the test solution is collected regularly, and an equal amount of PBS is supplemented. The content of the therapeutic agent in the collected test solution is determined by high performance liquid chromatography (HPLC), and compared with the total amount of the therapeutic agent loaded in the product, the cumulative release rate of the therapeutic agent is calculated.
[0149] The results of in vitro testing of drug release performance for promoting tissue regeneration and repair are shown in Figure 1 and 2 , the release period of various drugs promoting tissue regeneration and repair prepared by the scaffolds in Examples 1 to 4 exceeds 5 weeks. Comparative Example 1 does not use gluconolactone, and its scaffold fiber does not contain a porous structure, and its drug release rate is significantly lower than that of Example 1; Comparative Examples 2 and 4 do not perform ZIF8 surface modification, and the burst release is significantly increased compared with Example 1, and the release rate is significantly increased, and the release is basically completed in 5 weeks. The drug-loaded polydopamine particles in Comparative Example 6 do not contain bioactive ceramics, which has little effect on the release of the drug, and the release curve is close to that of Example 1. Comparative Example 7 does not contain polydopamine, and the burst release is significantly increased compared with Example 1, and the release rate is significantly increased, and the release is basically completed in 4 weeks.
[0150] The results of in vitro antimicrobial drug release performance test are shown in Figure 3 and 4 , the release period of various antibacterial drugs for the stents prepared in Examples 1 to 4 exceeds 3 weeks. Comparative Example 1 does not use gluconolactone, and its stent fiber does not contain a porous structure, and its antibacterial drug release rate is close to that of Example 1; compared with Example 1, the changes in Comparative Examples 5 to 8 have little effect on the release of antibacterial drugs embedded on the stent surface, and the release curves are close to that of Example 1; Comparative Example 2 does not contain a ZIF8 layer, and the antibacterial drugs are directly adsorbed on the stent surface. Compared with Example 1, the burst release is significantly increased, and the release rate is significantly accelerated, and the release is basically completed in 1 week.
[0151] 4. In vitro osteogenic differentiation test of preosteoblasts
[0152] The composite materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were irradiated and sterilized, and then immersed in DMEM basal culture medium at a concentration of 10 mg / mL, and placed in a 37°C shaker at 120 rpm for 24 hours. After the extraction, the mixture of the composite material and the culture medium was centrifuged at 1000 rpm and the supernatant was collected. The collected extracts were diluted 2 times with the corresponding DMEM culture medium, and finally 10% fetal bovine serum was added to obtain a conditioned medium.
[0153] MC3T3-E1 cells were plated at 1×10 5The cells were inoculated in a 24-well plate at a density of 100 μg / mL. After 24 hours of adherent culture, the conditioned medium was replaced and cultured in an incubator at 37°C and 5% carbon dioxide atmosphere. The culture medium was replaced every 2-3 days. After 7 days of culture, the osteogenic differentiation performance of MC3T3-E1 cells was detected by the alkaline phosphatase secreted by them and measured by the pNPP method. The specific steps are as follows: After the cells were washed with PBS solution, they were immersed in a PBS solution containing 0.1 mol / L glycine, 1 mmol / L magnesium chloride and 0.05% Triton X-100 (octoxynol). After the cells were dissolved, the dissolved solution was evenly mixed with disodium p-nitrophenyl phosphate, and the mixed solution was placed at 37°C for 30 minutes. Subsequently, the mixed solution was added dropwise to a 96-well plate, and the absorbance of each well at a wavelength of 405 nm was measured using an ELISA reader.
[0154] Definition of alkaline phosphatase activity unit: In diethanolamine (DEA) buffer at pH 9.8, at 37°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one DEA enzyme activity unit. In glycine buffer at pH 9.6, at 25°C, the amount of alkaline phosphatase required to hydrolyze para-nitrophenyl phosphate chromogenic substrate to produce 1 micromole of p-nitrophenol per minute is defined as one enzyme activity unit, also known as one Glycine enzyme activity unit. One Glycine enzyme activity unit is approximately equivalent to 3 DEA enzyme activity units. According to the definition of enzyme activity, calculate the alkaline phosphatase activity in the sample and plot it separately, as shown below. Figure 3 shown.
[0155] Depend on Figure 5It can be seen that the scaffolds in Examples 1 to 4 of the present invention have a good effect of inducing cells to secrete alkaline phosphatase, but in the case of using gluconolactone, Comparative Example 1 does not have a gradient pore structure, and its cell activity is not as good as that with a gradient pore structure, which also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is slightly reduced compared with Example 1. Comparative Example 3 is not loaded with antibacterial drugs, and the alkaline phosphatase activity is close to that of Example 1. The drug-loaded polydopamine particles in Comparative Example 6 do not contain bioactive ceramics, which also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is also slightly reduced compared with Example 1. Comparative Examples 2 and 4 do not contain a ZIF8 layer with good biological activity, and the alkaline phosphatase activity is significantly reduced compared with Example 1. Comparative Example 7 does not contain polydopamine with osteogenic activity, but at the same time, the release of the drug is significantly accelerated, which also affects the cell secretion of alkaline phosphatase, and the alkaline phosphatase activity is also significantly reduced compared with Example 1. The bioactive ceramic / polydopamine particles in Comparative Example 5 were not loaded with drugs, and the alkaline phosphatase activity was significantly decreased compared with Example 1. Comparative Example 8 did not contain drug-loaded bioactive ceramic / polydopamine particles, and the alkaline phosphatase activity was also significantly decreased compared with Example 1, and its alkaline phosphatase activity was lower than that of Comparative Example 5. Comparative Example 9 did not contain a ZIF8 layer with good biological activity, nor did it have a gradient pore structure, drug-loaded mesoporous ceramic@polydopamine particles, and antibacterial drugs, and its alkaline phosphatase activity was the lowest.
[0156] 5. Antibacterial performance test of stent
[0157] Take fresh slant cultures of Staphylococcus aureus and Escherichia coli, count the live bacteria in the bacterial suspension, and prepare a diluent (1% peptone in 0.03 mol / L PBS (pH = 7.2-7.4)) to a bacterial count of 5 × 10 5 ~10×10 6 cfu / mL of bacterial suspension. Place the samples in sterile plates, add 50μL of bacterial suspension to each sample, record the time of adding bacteria to each tube, inoculate the blood plate 60min after adding bacteria, and place the samples in a 5mL nutrient broth tube. Incubate the blood plate and broth tube inoculated with bacteria at 37℃ for 48h, observe the preliminary results, and continue to culture in the sterile growth tube until the 28th day. If the broth tube is turbid and the blood plate has bacterial growth, it is recorded as positive, indicated by (+); if it is still clear on the 35th day, it is considered as sterile growth, indicated by (–).
[0158] Table 3 Antibacterial effect of the stents prepared in the examples and comparative examples
[0159]
[0160]
[0161] As shown in Table 3, the composite scaffolds prepared in Examples 1 to 4 of the present invention and Comparative Examples 1, 5 to 8 all have good long-term antibacterial effects and can grow aseptically for 35 days. Comparative Examples 2, 3, 4 and 9 do not contain ZIF8 or antibacterial drugs and do not have antibacterial effects.
[0162] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A modified polycaprolactone composite material bracket, characterized in that: It includes a polycaprolactone support matrix, the surface of the polycaprolactone support matrix is loaded with a metal organic framework material, and the metal organic framework material is loaded with antibacterial drugs; the surface and interior of the polycaprolactone support matrix are distributed with interconnected pores, and the pores gradually increase from the surface of the polycaprolactone support matrix to the inside; drug-loaded materials are distributed in the polycaprolactone support matrix, and the drug-loaded materials include mesoporous ceramics, the interior of the mesoporous ceramics is filled with tissue regeneration and repair drugs, and the surface of the mesoporous ceramics is coated with polydopamine.
2. The modified polycaprolactone composite material bracket according to claim 1, characterized in that: The surface of the polycaprolactone composite material has holes with a size of 1-100 μm.
3. The modified polycaprolactone composite material bracket according to claim 1, characterized in that: The mesoporous ceramic is selected from at least one of mesoporous silicon, mesoporous calcium silicate, mesoporous magnesium silicate, mesoporous zinc silicate, mesoporous strontium silicate, mesoporous bioglass, and mesoporous hydroxyapatite; And / or, the mesoporous ceramic is particles with a particle size of 30 to 1500 nm.
4. The method for preparing the modified polycaprolactone composite material bracket according to any one of claims 1 to 3, characterized in that: The steps include: S1. Mixing the drug-carrying material, gluconolactone and polycaprolactone in a solvent to obtain a mixed solution, transferring the solution to a mold and placing the solution for a period of time to obtain a mixed material film; using the mixed material film as a printing material, 3D printing to obtain a scaffold with a gradient pore structure; After printing, the scaffold with gradient pore structure was immersed in water to remove gluconolactone and residual solvent; S2. Reacting the stent with a gradient pore structure, an antibacterial drug, 2-methylimidazole and a zinc source in water to obtain the modified polycaprolactone composite material stent.
5. The method for preparing the modified polycaprolactone composite material bracket according to claim 4, characterized in that: The preparation method of the drug-carrying material comprises the following steps: immersing the mesoporous ceramic in a solution containing a drug for promoting tissue regeneration and repair to obtain a mesoporous ceramic encapsulating the drug for promoting tissue regeneration and repair; immersing the mesoporous bioceramic encapsulating the drug for promoting tissue regeneration and repair in a solution containing dopamine to obtain a drug-carrying material.
6. The method for preparing the modified polycaprolactone composite material bracket according to claim 4, characterized in that: The mass ratio of the drug-carrying material to polycaprolactone is (0.005-0.05):
1. And / or, the mass ratio of gluconolactone to polycaprolactone is (0.5-3):
1.
7. The method for preparing the modified polycaprolactone composite material bracket according to claim 4, characterized in that: The process conditions of the 3D printing meet at least one of the following: a) 3D printing uses a printing needle with a diameter of 0.15-0.4mm; b) Printing and heating temperature: barrel 60~80℃, needle 60~90℃; c) Fiber spacing 0.8mm×0.8mm; printing speed 8~17mm / s; d) Air pressure is 320-400Kpa; e) The height of the stent layer is 75-95% of the needle diameter.
8. The method for preparing the modified polycaprolactone composite material bracket according to claim 4, characterized in that: In step S1, the mixing time is 30-100 hours; And / or, the placement time is 50-100h.
9. The method for preparing the modified polycaprolactone composite material bracket according to claim 4, characterized in that: The mass ratio of the 2-methylimidazole, the antibacterial drug and the zinc source is (18-23):(4-10):1; And / or, the zinc source is zinc nitrate.
10. Use of the modified polycaprolactone composite material scaffold according to any one of claims 1 to 3 in the preparation of products for promoting bone tissue repair and regeneration.
Citation Information
Patent Citations
Nanoporous magnesium silicate microsphere / PBS (poly(butylene succinate)) composite scaffold, composite scaffold coated with protein, preparation methods and application
CN107412856A
Preparation method and application of nanofiber material taking polycaprolactone as matrix
CN115737909A
Gradient 3D printing polycaprolactone modified scaffold for repairing growth plate as well as preparation method and application of gradient 3D printing polycaprolactone modified scaffold
CN115887775A
SORAFENIB-INCORPORATED POLY(ε-CAPROLACTONE) FILM AND ITS DRUG-ELUTING STENT
KR1020120098208A
Biodegradable scaffolds
US20170136154A1